Hesitant Fuzzy Prime Ideal of Γ- ring - Karim, Mazen Omran; Ghanim, Rand Shafea (JOURNAL OF ADVANCES IN MATHEMATICS, 2022)
In this paper, we introduce the notions of hesitant fuzzy ideal, hesitant fuzzy prime ideal, hesitant fuzzy strongly prime ideal in gamma rings and hesitant 3-prime ideal. Also, we study the relation between the above concepts